Conceptual Framework for Financial Reporting - The International Financial Reporting Standards Foundation (The International Financial Reporting Standards Foundation, 2024)
Chapter 1. The objective of general purpose financial reporting. Chapter 2. Qualitative characteristics of useful financial information. Chapter 3. Financial statements and the reporting entity. Chapter 4. The elements of financial statements. Chapter 5. Recognition and derecognition. Chapter 6. Measurement. Chapter 7. Presentation and disclosure. Chapter 8. Concepts of capital and capital maintenance